Critical assessment of Islamic endowment funds (Waqf) literature: lesson for government and future directions. Issue 10 (October 2020) - Sukmana, Raditya
Abstract: In this paper, the literature on Islamic endowment funds (awqaf) was surveyed. The data suggest that banking, accountability, law, and norms constitute most of the coverage in this body of literature. The finance topic, with 35% coverage, dominated the literature, whereas history (with 6% coverage) recorded the least interest. In this sample, the second most popular theme was related to economic development (25% coverage). Also discovered was that 59% of the papers employed a normative approach, and the balance adopted an empirical approach. A direct benefit of this study is that it provides input for government policy and directions for future researchers. Abstract : Endowment Fund; Waqf; Awqaf, Islamic Economics; Islamic Social Finance; Public economics; Economic Development; Economic Growth; Research and development; Religion.